2014
DOI: 10.1136/bcr-2013-201637
|View full text |Cite
|
Sign up to set email alerts
|

An unusual association of autosomal polycystic kidney disease and multiple myeloma

Abstract: Autosomal dominant polycystic kidney disease (ADPKD) is well known for its different renal and extrarenal complications. Chronic renal failure (CRF) from ADPKD is also reported in older patients. On the other hand, multiple myeloma (MM) can also cause renal damage by different mechanisms. A 38-year-old man presented with dull aching abdominal pain, recent onset respiratory distress along with bilateral pedal swelling. Initial investigations revealed polycystic kidney disease but subsequently it was found that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
1
0
0
Order By: Relevance
“…Bipedal swelling and flank pain are common symptoms reported in patients with ADPKD. In consonance with the study of Mandal et al, [20], we observed bipedal swelling and flank pain among our participants. Bipedal swelling usually occurs due to the lower serum oncotic pressure from the nephrotic proteinuric range characteristic of kidney disease whereas flank pain results directly and indirectly from cyst formation and enlargement on kidneys and sometimes, nearby organs such as the liver [21].…”
Section: Discussionsupporting
confidence: 93%
“…Bipedal swelling and flank pain are common symptoms reported in patients with ADPKD. In consonance with the study of Mandal et al, [20], we observed bipedal swelling and flank pain among our participants. Bipedal swelling usually occurs due to the lower serum oncotic pressure from the nephrotic proteinuric range characteristic of kidney disease whereas flank pain results directly and indirectly from cyst formation and enlargement on kidneys and sometimes, nearby organs such as the liver [21].…”
Section: Discussionsupporting
confidence: 93%